Analisis Kompetensi Dan Disiplin Kerja Personel Intelijen KODAM Jaya Terhadap Kesuksesan Operasi Gabungan TNI - Ainur Rofiq, Dwi; Lestari, Amin; Nendya Rahadyaning P, Bima (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
In the context of joint operations within the Indonesian National Army (TNI), the success of missions is heavily influenced by the competence and discipline of intelligence personnel. The Kodam Jaya intelligence unit faces challenges related to the effectiveness of its analytical skills, procedural compliance, and coordination with operational units. These challenges potentially hinder the overall effectiveness of joint operations. This study aims to evaluate how the competence and work discipline of Kodam Jaya's intelligence personnel affect the success of joint TNI operations. The research seeks to identify weaknesses in analytical skills, procedural adherence, and communication, and provide recommendations for improvement. A qualitative research approach was employed, utilizing primary and secondary data sources. Primary data were collected through in-depth interviews and direct observations of intelligence personnel during joint operations. Secondary data included operational documents and existing literature on military intelligence. Data were analyzed using a systematic qualitative approach, involving coding, categorization, and interpretation to derive meaningful insights. The analysis revealed significant gaps in the analytical competencies of intelligence personnel, affecting the accuracy and effectiveness of data processing and decision-making. Procedural compliance was inconsistent, leading to breaches and operational risks. Communication and coordination between intelligence and operational units were often ineffective, impeding timely responses to threats. Practical experience was found to be crucial for performance, yet many personnel lacked adequate experience in joint operations. Motivation and work ethics varied, impacting the overall quality of intelligence tasks. The study concludes that enhanced training, improved communication systems, and strengthened motivation and ethics are essential for improving the effectiveness of intelligence operations and achieving successful joint missions.